Apertura de datos públicos de Ecuador en base a los principios de linked open data. - Maza Puchaicela, Liliana Alexandra (2014)
The present research work is based on the study of public data opening based on the principles of Linked Open Data (LOD) as an alternative to demonstrate transparency, participation and collaboration between the Ecuadorian government and citizenship, and the improvement of existing communication between them. The opening data has contributed to the development of the countries that have adopted the initiative, demonstrating transparency in their governments, through a better communication between citizens and government. To do the public data opening of Ecuador, the theme about the state of art has been investigated, and on this basis has been studied success stories in America and Europe so that it is possible to determine the appropriate methodology for Ecuadorian government. The methodology for the public data opening from Ecuador based on the principles of LOD is described and implemented through the creation of the data set of the tourist attractions of Loja city; data obtained from Tourism Ministry of Loja, and when they be released, they will contribute to the generation of a great tourism in the city, and when the methodology of releasing data be applied, it is obtained as result, files of them in RDF (Resource Description Framework) and JSON (JavaScript Object Notation). Finally the data are reused according to the obtained formats and the mobile application "ATL", develop according to the Android programming language and with the access of released public data in Json format hosted on the portal datosabiertos.ec, is obtained.